Um breve comentário sobre equações diferenciais de primeira ordem - EMIDIO, Rafael Sergio Sampaio (2023)
In this paper we present a brief study of first order ordinary differential equations. We study some analytical methods for determining solutions and important applications in cer tain areas of human knowledge; such as biology, chemistry, physics, and mathematics, in volving these classes of equations and methods.